Nanoparticles - Jelinek, Raz (De Gruyter graduate., 2015)
Nanoparticles presents the variety of nanoparticle families, structures, and functions. The book discusses nanoparticles made of semiconductors, metals, metal-oxides, organics, biological and hybrid constituents. Through a wealth of examples and case studies, readers that are not necessarily active or experts in this area acquire a broad overview of this exciting field at the interface between scientific research and practical technologies.